The survival of blown pack spoilage associated Clostridium estertheticum and Clostridium gasigenes spores during the ensiling of grass. (2nd October 2021) - Esteves, Eden; Whyte, Paul; Gupta, Tanushree B; Bolton, Declan
ABSTRACT: Blown pack spoilage (BPS) of vacuum packaged primals, caused by Clostridium estertheticum and Clostridium gasigenes, is a serious issue for the beef industry. There are multiple sources of these bacteria on beef farms, including grass and associated feed preparations. The aim of this study was to investigate the survival of C. estertheticum and C. gasigenes spores during the ensiling of grass and the subsequent opening of the silos. Grass, harvested from fields, with and without cattle slurry amendment, was inoculated with approximately 100 spores/g and ensiled using a laboratory (silo) model system at 20°C in the dark. Adding formic acid or sucrose resulted in six treatment combination as follows: no slurry (NS), no slurry plus formic acid (NSFA), no slurry plus sucrose (NSS), slurry (S), slurry plus formic acid (SFA) and slurry plus sucrose (SS). During the silage fermentation, samples were removed periodically and tested for C. estertheticum, C. gasigenes, total viable, Escherichia coli, Enterobacteriaceae and lactic acid bacteria (LAB) counts. The pH, ethanol, volatile fatty acids (VFA), lactic acid and ammonia concentrations were also monitored throughout the experiment. C. estertheticum did not survive the ensiling process, regardless of treatment. In contrast, C. gasigenes grew in the early stages and was detected during the entirety of the fermentation for all treatments. Based on these observations, it was concluded that the silage fermentation process described would not remove C. gasigenes and contaminated grass may result in contaminated feed for animals.